Mejoramiento y Rehabilitación del Canal de Regadío Carabamba margen izquierda, Distrito de Carabamba, Provincia de Julcán, Departamento de La Libertad - Aredo Moya, Antonio Erick (2016)
The hydraulic planning for irrigation this thesis considers the execution of a left bank canal which have the following characteristics: - Partidor: gate type concrete fc = 175 kg / cm2 with measures 0.70 x 0.70 m and a thickness of 0.15 m. - Left Bank Canal: concrete channel 0.60 x 0.60 m and 0.10 m thick. and a length of 6168.9 m. - Air Pass: concrete with iron mesh of 26.25 x 1.0 m and a thickness of 0.10 m. and 26.25 m in length. - Side Shot: concrete with stone masonry 0.90 x 0.30 m and a thickness of 0.10 m. - Posas dissipative: are of different concrete measures arming fc = 210 kg / cm2 for walls and floors, steel armor f'y = 4200 kg / cm2 and minimum cover of 4 cm. The development of this thesis aims to develop engineering studies, and the following scheme was taken into account: The topographic survey, taquimétrico uprising, fieldwork and cabinet for the generation of longitudinal profile that will provide the best location of water intakes and projected rectangular channel. The hydrological study to determine the maximum and minimum flow rates to provide us with the data for the design of irrigation canal. The description of the technical specifications, which are taken into account at the time of project implementation. The study of soil mechanics, their general, physical properties of the land where irrigation structures will be built. the metrado, costs and budget of this project is also described. the environmental impact study is also described to develop proper management in environmental management in the area where the work is performed. And finally the conclusions and recommendations that were reached following the development of this project are presented.